Colloidal nano-MOFs nucleate and stabilize ultra-small quantum dots of lead bromide perovskites. Issue 17 (30th March 2021) - Protesescu, Loredana; Calbo, Joaquín; Williams, Kristopher; Tisdale, William; Walsh, Aron; Dincă, Mircea
Abstract : We demonstrate a simple and effective host–guest strategy for preparing ultra-small lead bromide perovskite QDs through the use of nano-sized MOFs that function as nucleating and host sites. Abstract : The development of synthetic routes to access stable, ultra-small ( i.e. <5 nm) lead halide perovskite (LHP) quantum dots (QDs) is of fundamental and technological interest. The considerable challenges include the high solubility of the ionic LHPs in polar solvents and aggregation to form larger particles. Here, we demonstrate a simple and effective host–guest strategy for preparing ultra-small lead bromide perovskite QDs through the use of nano-sized MOFs that function as nucleating and host sites. Cr3 O(OH)(H2 O)2 (terephthalate)3 (Cr-MIL-101), made of large mesopore-sized pseudo-spherical cages, allows fast and efficient diffusion of perovskite precursors within its pores, and promotes the formation of stable, ∼3 nm-wide lead bromide perovskite QDs. CsPbBr3, MAPbBr3 (MA + = methylammonium), and (FA)PbBr3 (FA + = formamidinium) QDs exhibit significantly blue-shifted emission maxima at 440 nm, 446 nm, and 450 nm, respectively, as expected for strongly confined perovskite QDs. Optical characterization and composite modelling confirm that the APbBr3 (A = Cs, MA, FA) QDs owe their stability within the MIL-101 nanocrystals to both short- and long-range interfacial interactions with the MOF pore walls.